2005
DOI: 10.1097/01.mao.0000185082.28598.87
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept Treatment for Autoimmune Inner Ear Disease: Results of a Pilot Placebo-Controlled Study

Abstract: The results of this pilot trial demonstrate that etanercept 25 mg twice weekly for 8 weeks was no better than placebo for treatment of AIED in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 13 publications
2
63
0
Order By: Relevance
“…10 While some investigators reported that, in an animal model, etanercept has a protective effect on hearing loss, 11 others found it less effective than prednisone, with a greater potential for adverse effects. 4,6,12 In 2 small human studies, levels of TNF in patients with sudden SNHL were found to be elevated in one study of 12 patients, 13 while the other study showed that both corticosteroid-responding and nonresponding patients (total of 30 for both groups together) had lower levels of TNF than controls and concluded that this cytokine does not offer useful information in either prognosis or diagnosis of the disease.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…10 While some investigators reported that, in an animal model, etanercept has a protective effect on hearing loss, 11 others found it less effective than prednisone, with a greater potential for adverse effects. 4,6,12 In 2 small human studies, levels of TNF in patients with sudden SNHL were found to be elevated in one study of 12 patients, 13 while the other study showed that both corticosteroid-responding and nonresponding patients (total of 30 for both groups together) had lower levels of TNF than controls and concluded that this cytokine does not offer useful information in either prognosis or diagnosis of the disease.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%
“…Vari-ous cytokines have been implicated in IM-SNHL, such as interleukin (IL)-1␤, 2 interferon (IFN)-␥, 3 and tumor necrosis factor (TNF; formerly known as tumor necrosis factor ␣). 4 Several clinical trials have been conducted in this patient population with immunemodulating agents such as methotrexate, 5 etanercept, 4,6,7 and infliximab, 8 all with limited success. Ren et al 9 reported on TNF in patients with sudden SNHL and progressive SNHL in 1998.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%
“…Prior to these studies, no effective therapies have been identified for corticosteroidresistant AIED patients. Moreover, no alternative effective therapies have been identified in corticosteroid-sensitive patients (14,16,17). Finally, even gains in steroid-sensitive AIED patients using corticosteroid therapy may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab has also been reported to be effective in the treatment of autoimmune sensorineural hearing loss 2 . Etanercept has had contrasting results in this setting, mostly negative 3,4 . We recently encountered 2 cases of sensorineural hearing loss temporally related to adalimumab.…”
Section: To the Editormentioning
confidence: 99%